The novel quinoline derivative SKA-346 as a KCa3.1 channel selective activator - Wong, Brandon Han Siang (2025)
The calcium-activated KCa3.1 channel plays a crucial role in T-cell immune response. Genetic manipulation of T-cells to upregulate the expression of K+ channels has been shown to boost T-cell cytotoxicity in cancer. Here, we aimed to identify and characterize an activator that would augment KCa3.1 currents without affecting other channels. We synthesized five quinoline derivatives and used electrophysiology to screen them on KCa3.1 and a panel of 14 other ion channels. One quinoline derivative, SKA-346, activated KCa3.1 with an EC50 of 1.9 μM and showed selectivity against the other channels. In silico analysis using RosettaLigand and GLIDE demonstrated a well-converged pose of SKA-346 in a binding pocket at the interface between the calmodulin N-lobe and the S45A helix in the S4-S5 linker of the KCa3.1 channel. SKA-346 (30 mg kg-1), tolerated by mice after intra-peritoneal administration, exhibited a peak plasma concentration of 6.29 μg mL-1 (29.2 μM) at 15 min and a circulating half-life (t 1/2) of 2.8 h. SKA-346 could serve as a template for the development of more potent KCa3.1 activators to enhance T-cell cytotoxicity in cancer.